A Systematic Literature Review of Digital Marketing Ethics Practices in Micro, Small, and Medium Enterprises in Indonesia - Santoso, Ruth Natallie; Nugroho, Monica Clarissa Noni; Aritonang, Amelia; Rizqiyah, Dwi Anggraeni; Fachmi, Muhammad (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Abstract. The rise of digital technology has transformed business marketing, especially for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, where the digital economy is expected to reach USD 90 billion. This growth drives MSMEs to adopt digital marketing, yet it also raises ethical concerns such as data misuse, misleading content, hoaxes, and algorithm manipulation. These issues are intensified by low digital literacy, market pressures, and weak regulations. This study aims to analyze how ethical principles are integrated into digital marketing practices among Indonesian MSMEs. Using a qualitative descriptive method through literature review, the study identifies limited ethical awareness and application among MSMEs, despite growing recognition of its importance. Challenges include lack of knowledge, resources, and ethical guidance. However, applying core values like transparency, honesty, and social responsibility proves vital for building consumer trust and long-term business sustainability. The study concludes that structured integration of ethics into MSME digital marketing is crucial and offers practical recommendations to promote responsible and sustainable practices in Indonesia’s digital economy.